Kegagalan Calon Perempuan dalam Pemilukada Kabupaten Merangin Tahun 2013 (Studi Kasus Fauziah, SE) - Syalfia .; Susilo Utomo; Fitriyah . (Journal of Politic and Government Studies, 2015)
ABSTRACTThis research was done to convey the failure of female candidate in the election of mayor of Merangin in Jambi Province in 2013 because only in 2013 female candidate appears in the election of mayor of Merangin in Jambi Province. The method of this research used qualitative approach and credible informant towards the process of regent and vice regent election. The result of this research was the failure of the female candidate in the election was caused by gender factor and political strategy. Every male and female candidates should be prepared themselves to socialize long before the election and participation of female candidate in political world will need all endorsement from every sides and the relevance of political education on women become very important to compete with male candidates.KEYWORDS: Women, Gender, Election